Can Self-Concept Clarity Protect against A Pandemic? A Daily Study on Self-Concept Clarity and Negative Affect during the COVID-19 Outbreak. Issue 1 (2nd January 2021) - Alessandri, Guido; De Longis, Evelina; Golfieri, Francesca; Crocetti, Elisabetta
ABSTRACT: Self-concept clarity reflects how confidently and clearly an individual defines the self-belief, and it is theorized to help individuals to be more resilient in the face of stressors. The present study aimed at investigating how self-concept clarity may be implicated in the stress process related to the COVID-19 outbreak, by examining its association with daily negative affect, as a short-term adaptational outcome. The impact of the total number of positive cases, as an objective index of COVID-19 spreading, on negative affect was also tested. Participants were 287 young Italian adults (52% female; Mage = 22.68 years, SDage = 2.62), who completed twelve daily diaries (of which five after the lockdown measure was introduced). Results from multilevel growth modeling showed that individuals low in self-concept clarity reported the highest levels of negative affect across the study period, compared to individuals high in self-concept clarity. Moreover, after the issuing of the lockdown measure, individuals high in self-concept clarity showed a steeper increase in their daily level of negative affect, compared to individuals low in self-concept clarity, indicating their responsiveness to the new situation. The total number of new cases was not related to daily negative affect. These findings attest the protective role of self-concept clarity and its impact on emotional responding to the lockdown measure in Italy.